Parents as coronavirus disease-19 carriers in intrafamily settings: Cases of severe forms in a family cluster - Tchidjou, Hyppolite K.; Ghida, Ghostine; Moreau, Francois; Joseph, Cédric; Romeo, Bernard (International Journal of Health Sciences, 2021)
The outbreak of coronavirus disease-19 (COVID-19) infection that started in China in December 2019 has subsequently spread too many countries worldwide with high contagiousness. Given the spread and the current debate on the management and origin of intrafamilial clusters of COVID-19, this case highlights how essential it has become to prompt quarantine for the whole family and any contact member who may be at risk of infection. For this, the management of family clusters requires specific guidelines that need to be prepared to help clinicians and families to better face the disease, especially the risk of developing severe forms. We reported a case and the management of severe forms of COVID-19 infection in an intrafamily cluster with different child and parent outcomes.